Factors related to depression in older adults during the COVID-19 pandemic in two coastal regions of Peru: An analytical cross-sectional study - Quispe Sáenz, Elena de Jesús (2022)
“Background: Mental health problems such as anxiety, depression and their aggravation have been studied extensively in the general population. However, there are few studies on depression in older adults and the few existing results may be contradictory, especially in the context of the COVID-19 pandemic. The aim of this study is to determine the factors associated with depression in older adults in two coastal regions of Peru during the COVID-19 pandemic. Methods: This study uses an analytical cross-sectional design in a population of older adults, who participated in a non-governmental ambulatory social support program in Callao and Ica, two coastal regions of Peru. We administered an on-site structured questionnaire to record sociodemographic data, the Geriatric Depression Scale by Yesavage to measure depression, and the Barthel Index to assess physical function. In order to determine cognitive impairment as an exclusion criterion, the MEC-30 was used. The association between variables was assessed through contingency tables, using the odds ratio (OR) with its corresponding confidence interval (95% CI) and the X2 test. Finally, a binary logistic regression analysis was performed. Results: Out of the 244 older adults surveyed, 39% had depressive symptoms, of which 28.3% (n=69) and 10.7% (n=26) were moderately and severely depressive, respectively. The findings significantly associated with the presence of depressive symptoms were being 76 years old or older [p=0.005, OR: 2.33, 95% CI: 1.29-4.20], not participating in weekly recreational activities [p=0.004, OR: 2.28, 95% CI: 1.31-3.99] and the presence of comorbidities [p=0.026, OR: 1.88, 95% CI: 1.07-3.29]. Conclusion: There are few studies exploring depression in older adults during the COVID-19 pandemic; this research shows the importance of mental health care in this population and, particularly, of those who are 76 or older because they suffer from comorbid conditions and have interrupted recreational activities.“